2016
DOI: 10.1039/c6cy01378c
|View full text |Cite
|
Sign up to set email alerts
|

Solubility product difference-guided synthesis of Co3O4–CeO2 core–shell catalysts for CO oxidation

Abstract: Co3O4–CeO2 core–shell catalysts are successfully fabricated by an ion exchange procedure between Co(CO3)0.35Cl0.2(OH)1.1 nanorods and Ce3+ aqueous solution, followed by a calcination step.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(13 citation statements)
references
References 38 publications
0
13
0
Order By: Relevance
“…In recent years, transition-metal oxides have become popular as non-noble metal catalysts [20][21][22][23][24][25][26], and their CO oxidation performance has been reported to be strongly influenced by the catalysts' structure, size, and morphology [27]. Chen et al [28] synthesized Co 3 O 4 -CeO 2 core-shell catalysts and proved that the synergistic effect between Co 3 O 4 and CeO 2 is responsible for their enhanced catalytic activity compared with that of regular catalysts. Narayana et al [29] prepared spherical CeO 2 nanoparticles with Mn-ion substitution and observed the highest CO oxidation rate for the structure with the highest amounts of Mn 2+ as well as oxygen vacancies.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, transition-metal oxides have become popular as non-noble metal catalysts [20][21][22][23][24][25][26], and their CO oxidation performance has been reported to be strongly influenced by the catalysts' structure, size, and morphology [27]. Chen et al [28] synthesized Co 3 O 4 -CeO 2 core-shell catalysts and proved that the synergistic effect between Co 3 O 4 and CeO 2 is responsible for their enhanced catalytic activity compared with that of regular catalysts. Narayana et al [29] prepared spherical CeO 2 nanoparticles with Mn-ion substitution and observed the highest CO oxidation rate for the structure with the highest amounts of Mn 2+ as well as oxygen vacancies.…”
Section: Introductionmentioning
confidence: 99%
“…In the fitted spectrum of Co, peaks from Co­(CO 3 ) 0.35 Cl 0.2 (OH) 1.1 were also observed which could be because of growth on the surface. Co­(CO 3 ) 0.35 Cl 0.2 (OH) 1.1 is widely used as a precursor for the growth of Co 3 O 4 nanowires. , Further, no traces of this impurity phase was observed in XRD, confirming the growth of CoMoO 4 as a major crystalline phase. The binding energy at 529.79 eV corresponds to O 1s of CoMoO 4 as shown in Figure c and the satellite peak at 531.70 eV is attributed to the surface impurity as observed in the Co 2p edge.…”
Section: Resultsmentioning
confidence: 89%
“…The peak at a higher binding energy (Oα: 531.5 eV) was derived from the adsorptive oxygen species. Apart from the insignificant influence from the surrounding atmosphere, the XPS data was complementary to other techniques insofar as showing the successful synthesis of the Co 3 O 4 –CeO 2 hierarchical nanotubes.…”
Section: Resultsmentioning
confidence: 99%
“…Synergistic effects have also been observed if CeO 2 coexists with other transition‐metal‐based catalysts such as CeO 2 –Fe 2 O 3 , CeO 2 –CuO and CeO 2 –MnO 2 . Therefore, there is reason to believe that the hierarchical structure of a Co 3 O 4 –CeO 2 composite material would exhibit good performance toward CO oxidation . Additionally, CO oxidation can be significantly influenced by the morphology of the material.…”
Section: Introductionmentioning
confidence: 99%